Positive thermal expansion facilitates the formation of argentophilic forces following an order–disorder phase transition. (10th May 2021) - Juneja, Navkiran; Unruh, Daniel K.; Groeneman, Ryan H.; Hutchins, Kristin M.
Abstract : Variable-temperature studies of the 0D silver-based complex [Ag2 (CF3 SO3 )2 (4-SB)4 ] reveal formation of argentophilic forces upon warming due to a phase transition. Abstract : Argentophilic forces are formed in a coordination complex based on silver(i ) trifluoromethanesulfonate and 4-stilbazole as a ligand. The forces are absent at low temperature and form as a result of an order–disorder phase transition that occurs upon heating. Colossal positive thermal expansion also precedes the phase transition.